Pemanfaatan Media Pembelajaran Berbasis Joyfull Learning Untuk Siswa Sd : Kajian Literatur - Hilda Riskika Septina; Natasya Nisau Syifa; Nayla Anggraeni Nur Khafidoh; Rani Setiawaty (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2026)
This study aims to synthesize and map findings from various studies on the use of joyful learning-based instructional media for elementary school students through a systematic literature review approach. The method used is Systematic Literature Review (SLR) with data sources obtained through searches on the Google Scholar and Publish or Perish (PoP) databases. The articles reviewed were limited to the period 2020 to 2026 with elementary school students as the research subjects. The results of the review reveal three main findings. First, joyful learning-based instructional media comes in various forms ranging from technology-based media such as flash multimedia and Augmented Reality, game-based media such as Treasure Hunt GPS, board games, game matching, and gamification, to contextual approaches that connect learning materials with students' real-life experiences, with the main characteristics of being active, interactive, and contextual. Second, the use of joyful learning-based media is carried out through structured stages including designing a conducive and enjoyable learning atmosphere, actively and interactively delivering learning materials, as well as appreciative reflection and reinforcement. Third, the use of joyful learning-based instructional media has proven effective in improving the quality of students' learning processes and outcomes comprehensively, covering cognitive, affective, and psychomotor domains. The conclusion of this study confirms that joyful learning supported by appropriate instructional media is a systematic effort in realizing quality, humanistic, and student-centered elementary education that focuses on the overall development of learners.